Diabetes medication prescribing trends based on provider type and location in the United States - Susan D. Meeke; Megan M. Weemer (Preventive Medicine Reports, 2025)
Background: As primary care physician numbers continue to decline, more patients with type 2 diabetes are likely to receive care from advanced practice providers (APPs), including physician assistants and nurse practitioners. Analyzing diabetes medication prescribing trends among these provider types is essential for ensuring evidence-based diabetes care. Purpose: This retrospective, cross-sectional pilot study aimed to examine differences in type 2 diabetes medication prescribing trends by provider type (physicians vs. APPs) and geographic location, utilizing National Ambulatory Medical Care Survey (NAMCS) data. Methods: Data from the NAMCS were collected in August 2022 for the years 2015, 2016, 2018 and analyzed using IBM SPSS, employing chi-square analysis to assess associations between provider type, geographic location, and prescribed medications. Frequency distributions were calculated for patient characteristics and provider types. Results: Patients prescribed at least one diabetes medication (N = 1444) were included. Most received care from physicians (93.7 %) in metropolitan areas (82.8 %). Statistically significant associations were found between provider type, geographical location, and medications prescribed. Nurse practitioners were more likely to prescribe newer diabetes medications, while physician assistants frequently prescribed basal insulin. Patients in non-metropolitan statistical areas were more often prescribed older medications, whereas those in the West were less likely to receive older medications. Conclusions: The study revealed distinct prescribing patterns by provider type and geographic location. Notably, APPs tended to prescribe newer or specific medications in certain locations, highlighting the influence of provider type and geography on diabetes care. Further studies should include larger samples of APPs to deepen insights into these trends.